Investigation on behaviours of spalling for the railway wheel steel under cyclic rolling contact - Luo, Dengfeng (Nanyang Technological University, 2020)
Due to punctuality and efficiency, Singapore's MRT has become one of the most popular modes of transportation. During train operating there are many different types of defects such as spalling, flange breakage, adhesive. Although the damage mechanism of each type of defect is different, major influential factors is interface condition between railway and wheels. When train was served for a long term, a surface layer called white etching layer (WEL) would form which had reverse effect on the wheels service life. Spalling is one kind of rolling contact fatigue (RCF) damage for the railway wheel. Cracks often initiate in the WEL and then propagate into the wheel due to cyclic rolling contact. The cracked material may break away from the railway wheel, and can grow to bigger cracks and cause fracture. The project aims to investigation on behaviours of spalling for the railway wheel steel under cyclic rolling contact, and the crack initiation and propagation mechanism in wheels with white etching layer due to RCF. Use Extended Finite Element Method (XFEM) through Software ABAQUS to carry out different kind of simulations for the project. The focus of the project would be to analyse the relationship between various initial crack angles and crack propagation rates. In addition, a further study seeks to establish the relationship between different loads and varied material with the rate of crack propagation.